Increasing Severity of Spinal Cord Injury Results in Microglia/Macrophages With Annular-Shaped Morphology and No Change in Expression of CD40 and Tumor Growth Factor-β During the Chronic Post-injury Stage - Akhmetzyanova, Elvira Ruslanovna; Timofeeva, Anna Viktorovna; Sabirov, Davran Khudaishukurovich; Kostennikov, Alexander Alexandrovich; Rogozhin, Alexander Alexandrovich; James, Victoria; Arkhipova, S. S.; Rizvanov, Albert Anatolevich; Mukhamedshina, Yana Olegovna (Frontiers in Molecular Neuroscience, 2022)
Determination of the quantitative composition of phenotypically and morphologically different populations of resident microglia and infiltrating macrophages in spinal cord injury (SCI) of various degrees of severity could lead to much needed novel therapeutic interventions in neurotrauma. In this regard, we investigated the CD40 and TGF-β expressing populations of microglia/macrophages and their morphological states in a rat model of SCI of varying severity. We are the first to describe the annular-shaped microglia/macrophages, the morphology of which was formed due to the spatial orientation of the processes that form round or oval micro-territories, which include disintegrating myelin fibers. This type of cell morphology was found only in the injured spinal cord and mainly in the white matter. At the same time, an assessment of the number of annular-shaped microglia/macrophages and the diameter of micro-territories formed by their processes showed an elevation in these indicators as the severity of SCI increased. While we did not find significant quantitative changes in the populations of Iba1+/CD40+ and Iba1+/TGF-β+ microglia/macrophages with increased severity of SCI in the chronic period (60 dpi), we did determine changes in the expression of cytokines and mRNAs of genes-encoding microglial marker proteins, finding the greatest changes on days 7 and 14 after SCI between experimental groups with varying severity.